Examining The Influence Of Electronic Word Of Mouth, Brand Image, And Celebrity Endorse On Brand Awareness And Purchase Intention. (A Case study of Padang Payakumbuah Restaurant) - Poan, Roy; Salsadella, Tri Chellin (International Journal of Family Business Practices, 2025)
Purpose - The purpose of this study was to examine whether electronic word of mouth, brand image, and celebrity endorsement affect the purchase intention of consumers of Padang Payakumbuah BSD Restaurant with brand awareness mediation. Design/methodology/approach - This study used quantitative methods. Online questionnaires were distributed and collected from people who have eaten at Padang Payakumbuah BSD Restaurant. A total of 353 valid responses were collected using convenience and purosive sampling methods. To achieve the objectives of this study, an analysis was conducted using SEM, or Structural Equation model, for hypothesis testing. Findings - The results showed that brand awareness significantly influences the purchase intention of consumers of Padang Payakumbuah BSD Restaurant. In addition, brand awareness is significantly influenced by electronic word of mouth, brand image, and celebrity endorsements. Originality/value - This study is the first research on purchase intention in the culinary industry using electronic word of mouth, brand image, celebrity endorser, and brand awareness variables. In addition, this research is the first to examine the Padang Payakumbuah BSD Restaurant.